Análisis de la demanda eléctrica para realizar un diagnóstico de la calidad de energía en el hospital del Instituto Ecuatoriano de Seguridad Social (iess) de la ciudad de Ambato en el año 2015 - Basantes Tisalema, Juan Carlos (2016)
Nowadays, the analysis of growth of electricity demand worldwide has taken hold, focusing on service quality, depending on the regulator and the different electricity uses, in order to reduce problems related to power quality that may exist in the electrical system. This project is aimed to the analysis of electricity demand in order to a diagnostic of the product quality in the Social Security Ecuadorian Institute hospital (IESS) of Ambato city, proposing solutions to problems that occur in their facilities, improving the service to the citizenship. An analysis of the current situation where is the electrical system of hospital was made out, measurements were performed with the Flucke 1735 network analyzer in the general transformer, main boards and “subgrids” obtaining the electrical parameters with which it is operating….